Vitiligo- A surgical approach - Deepti Ghia; Somshukla Ray; Reshma Gadkari; Chitra Nayak (Wolters Kluwer Medknow Publications, 2012)
Aims and objective- To describe the spectrum of surgical modalities for stable vitiligo patients Methods- Patients having stable vitiligo since past 2 years with no improvement with medical line of treatment were enrolled for surgery after informed consent. Depending upon the size and location of vitiligo patch different modalities were performed. Suction blister, mini-punch grafting, split thickness skin grafting, trypsinised melanocyte-keratinocyte transfer and non-trypsinised melanocyte- keratinocyte transfer (Jodhpur technique) and follicular grafting technique have been described photographically which have been performed at a tertiary care hospital. Conclusion- Vitiligo is often difficult to treat, stable patches resistant to medical line of management do respond to surgical treatment; however it is very important to choose the modality of surgery according location of the patch, size of the lesion and available resources.